Enhancing Viologen's Electrochromism by Incorporating Thiophene: A Step Toward All‐Organic Flexible Device. Issue 2 (11th December 2018) - Chaudhary, Anjali; Pathak, Devesh K.; Mishra, Suryakant; Yogi, Priyanka; Sagdeo, Pankaj R.; Kumar, Rajesh
Abstract : An all‐organic electrochromic device seems to be a possibility with ethyl viologen (EV) and poly‐3‐hexylthiophene (P3HT), both being organic materials, showing complementary electrochromic pair for color switching. The EV‐P3HT layer, sandwiched between ITO‐coated glass substrates shows switching between maroon and blue with an applied bias of 1.4 V. Mechanism of the color switching has been examined using UV‐Vis and Raman spectroscopies. The fabricated device shows optical modulation of 80%, switching time of 1 s while maintaining cycle life for a period of more than 600 s. The paradigm reported here inches toward realizing a flexible all‐organic electrochromic device. Abstract : This article features an electrochromic device consisting layers of viologen and thiophene. Polythiophene being a p‐type electrochromic material when combined with an n‐type viologen facilitates charge transport in viologen which is reflected in low voltage operation and improved coloration efficiency of device additionally giving an extra color to device, maroon.